Ecological predictors of academic satisfaction in senior secondary school students in Hong Kong: The mediating role of academic confidence - Dou, Diya; Shek, Daniel T. L.; Wong, Tingyin (Frontiers in Psychology, 2022)
Although the secondary school curriculum reform has taken place for more than one decade in Hong Kong, very few studies have examined the influence of academic stress, school support, positive youth development attributes, and academic confidence on academic satisfaction among senior secondary school students. This study was derived from a 6-year longitudinal project examining the youth development among Hong Kong adolescents. Only three waves of data collected from 2,023 students from grade 10 to grade 12 (i.e., Waves 4-6) were used in the present study focusing on senior high school years. We examined the impact of academic stress, school support, and positive youth development of students in Grade 10 on their academic satisfaction in Grade 12. Results showed that while Wave 4 academic stress negatively predicted academic satisfaction at Wave 6, Wave 4 positive youth development attributes and school support had positive associations with Wave 6 academic satisfaction; Wave 5 academic confidence also served as a mediator in these relationships, except for the relationship between school support and academic satisfaction. The theoretical, practical, and policy implications of the findings are discussed.